1984
DOI: 10.1128/aac.26.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of in vitro activities of cephalothin and ceftazidime with their efficacies in the treatment of Staphylococcus aureus endocarditis in rabbits

Abstract: Rabbits with Staphylococcus aureus endocarditis were treated with cephalothin or ceftazidime to determine whether differences in in vitro activity would result in differences in in vivo efficacy. Antibiotics were administered in doses equivalent to maximum recommended human doses, and results of laboratory tests to predict antimicrobial efficacy were determined during treatment. Cephalothin and ceftazidime MICs for the challenge strain were 0.5 and 8 ,ug/ml, respectively. MBCs were 32 and >128 ,ug/ml, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Controlled clinical data directly comparing the efficacies of these newer cephalosporins in patients who have staphylococcal bacteremia are unavailable. Previous animal model studies suggested that, for ceftazidime and staphylococci, in vitro data correlate poorly with in vivo efficacy (1,9). The experimental endocarditis model of infection represents a stringent test of vivo antibacterial activity, is highly reproducible, and offers the advantages of quantitative endpoints under defined experimental conditions and the ability to simultaneously compare several treatments. This study was designed to compare the relative antistaphylococcal activities in vivo of newer cephalosporins, including cefuroxime, cefoperazone, cefpirome, ceftazidime, ceftizoxime, cefotaxime, and ceftriaxone, in a rabbit model of experimental endocarditis.…”
mentioning
confidence: 99%
“…Controlled clinical data directly comparing the efficacies of these newer cephalosporins in patients who have staphylococcal bacteremia are unavailable. Previous animal model studies suggested that, for ceftazidime and staphylococci, in vitro data correlate poorly with in vivo efficacy (1,9). The experimental endocarditis model of infection represents a stringent test of vivo antibacterial activity, is highly reproducible, and offers the advantages of quantitative endpoints under defined experimental conditions and the ability to simultaneously compare several treatments. This study was designed to compare the relative antistaphylococcal activities in vivo of newer cephalosporins, including cefuroxime, cefoperazone, cefpirome, ceftazidime, ceftizoxime, cefotaxime, and ceftriaxone, in a rabbit model of experimental endocarditis.…”
mentioning
confidence: 99%
“…First generation cephalosporins are considered to be approximately equivalent in efficacy to nafcillin or oxacillin in vitro against MSSA and in the therapy of experimental endocarditis caused by MSSA. Third generation cephalosporins are less active than cefazolin or nafcillin in vitro against MSSA (Donowitz & Mandel, 1990) but animal model studies have suggested that this activity may not correlate well with in-vivo efficacy (Baker & Fass, 1984;McColm, Ryan & Acred, 1984).…”
Section: Infective Endocarditismentioning
confidence: 99%
“…These results are in agreement with those of other studies (1,5,6,27,30,32), suggesting that the newer cephalosporins and novel beta-lactams are probably as effective as combined aminoglycoside-beta-lactam treatment in severe bacterial It is also of interest that eight staphylococcal infections were successfully treated with CAZ, although the compound shows lower in vitro activity against staphylococci than cephalothin and oxacillin. Recently, CAZ has been shown to be as effective as cephalothin in the treatment of experimental staphylococcal endocarditis in rabbits (2). Although further investigation is warranted, it is apparent that CAZ possesses broad-spectrum activity against a large number of gram-positive and gram-negative agents.…”
mentioning
confidence: 99%